A three-colour flow cytometry technique for measuring trophoblast intracellular antigens: the relative expression of TAP1 in human cytotrophoblast and decidual cells. - Clover, L; Coghill, E; Redman, C; Sargent, I (2000)
Flow cytometry is conventionally used to measure cell-surface antigen expression. However, many antigens are found within the cytoplasm, and it is necessary to fix and permeabilize cells to enable antibodies to gain access to them. In this study we have established the conditions for studying intracellular antigens in human trophoblast cells by flow cytometry using an antibody to TAP1 (a key molecule in the process of Class I MHC assembly). We have previously shown by immunocytochemistry that TAP1 expression is apparently greater on Class 1 positive extravillous cytotrophoblast than on any other fetal or maternal tissue. However, as immunohistochemistry is not quantitative we have used three-colour flow cytometry to measure the expression of TAP1 in different trophoblast populations. Villous and extravillous cytotrophoblast were identified in first trimester and term placental and decidual digests on the basis of their expression of cytokeratin and Class I MHC antigens. The level of expression of TAP1 for each population was investigated using a commercial kit that determines the number of antibody-binding sites per cell. TAP expression was found to be three- to fivefold higher in extravillous cytotrophoblast, confirming our previous findings. The techniques developed here are directly applicable to the measurement of other intracellular molecules in trophoblast, in particular cytokines.